2018
DOI: 10.20944/preprints201801.0216.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hybrid GA-PSO Optimization of Artificial Neural Network for Forecasting Electricity Demand

Abstract: In the present study, a hybrid optimizing algorithm has been proposed using Genetic Algorithm (GA)and Particle Swarm Optimization (PSO) for Artificial Neural Network (ANN) to improve the estimation of electricity demand of the state of Tamil Nadu in India. The GA-PSO model optimizes the coefficients of factors of gross state domestic product (GSDP) , electricity consumption per capita, income growth rate and consumer price index (CPI) that affect the electricity demand. Based on historical data of 25 years … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…By combining this two methods, an optimized result can be achieved. (Anand and Suganthi 2018) use an ANN, which is optimized by a hybrid algorithm of GA and PSO.…”
Section: Hybrid Methodsmentioning
confidence: 99%
“…By combining this two methods, an optimized result can be achieved. (Anand and Suganthi 2018) use an ANN, which is optimized by a hybrid algorithm of GA and PSO.…”
Section: Hybrid Methodsmentioning
confidence: 99%
“…FSA incorporate to solutions in wireless sensor networks [30,32,33], tracking [34], medical estimations [35][36][37], segmentation [32], clustering [33], regression [38], image processing [39,40], calibration [35], localization [41], power systems [36,42].…”
Section: Applicationsmentioning
confidence: 99%
“…Therefore, we will save the first three best solutions and force other search agents (omegas) to update their position according to the position of the best search agents based on Eqs. (10)(11)(12)(13)(14)(15)(16).…”
Section: Detecting the Position Of The Preymentioning
confidence: 99%
“…Evaluations carried out by the error index indicate that the use of the genetic algorithm improves prediction performance up to 1.5%. In 2018, Anand and suganthi [11] proposed an ANN that is optimized with hybrid genetic algorithm and particle swarm optimization (GA-PSO) to predict the electricity demand of the state of Tamil Nadu in India. The obtained results showed that the proposed method have higher accuracy than single optimization models such as PSO and GA.…”
Section: Introductionmentioning
confidence: 99%